Anatomical Study of a Chimeric Fascio-Osteomyocutaneous Fibula Flap for Free Microvascular Tissue Transfer - Hamscha, Ulrike Maria; Weninger, Wolfgang Josef; Freystätter, Christian; Tzou, Chieh-Han; Radtke, Christine (Journal of Reconstructive Microsurgery, 2019)
Background Functional restoration in reconstructive surgery can require complex and adaptable approaches. In this anatomical study, the combined angiosome of the septofasciomyocutaneous vessels originating from the fibular artery was defined as basis for a chimeric flap of the lateral lower leg.Methods Methylene blue injection into the fibular artery was performed in 10 legs of fresh cadavers for visualization of the angiosome on the skin, fibula, and adjacent muscles as the lateral hemisoleus (HS) muscle. With regards to clinical specifications a maximum-size flap containing cutaneous, osseous, and muscular elements was raised. During dissection, the distribution pattern, number and size of stained septofasciomyocutaneous vessels at the lateral border of the proximal, middle, and distal thirds of the fibula length, as well as the flap dimensions were evaluated.Results In all specimens, vessels originating from the fibular artery and supplying the resected fibular bone, the fasciocutaneous flap and dorsally located muscles were found. The mean number of vessels to the skin was 4.2 per leg with a mean diameter of 1.1 ± 0.5 mm (range: 0.4–2.5 mm) and to the HS muscle 3.4 vessels with a mean diameter of 1.2 ± 0.7 mm (range: 0.3–3.0 mm). A total of 88.4% vessels occurred in the proximal and middle thirds of the legs. The resected fibula graft had a mean length of 23.8 ± 3.9 cm (range: 19.9–31.0 cm) and the skin paddle had a mean size of 23.8 ± 3.9 cm (range: 19.9–31.0 cm) × 7.0 cm. The flexor hallucis longus (FHL) muscle had a mean volume of 37.2 ± 15.8 cm3 (range: 18–58 cm3) and the lateral HS muscle 77.1 ± 23.3 cm3 (range: 48–105 cm3).Conclusion Our results and anatomical descriptions indicate that chimeric fibula flaps can meet the specific reconstructional requirements of complex and large sized defects representing a promising basis for further studies.
Keywords: free microvascular tissue transfer; chimeric osteomyocutaneous fibula flap; septofasciomyocutaneous vessels